Significance of Elevated Synovial Fluid Lactic Acid and Lactate Dehydrogenase Levels in Differentiating Between Septic Arthritis, Inflammatory Arthritis and Non-Inflammatory Arthritis - Erum, Uzma; Umer, Tahira Perveen; Arain, Shafiq-ur Rehman; Ahmed, Muhammad Rashid; Nazir, Lubna (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the lactic acid and lactate dehydrogenase levels in synovial fluid and differentiate between inflammatory and non-inflammatory arthritis.Study Design: Cross-sectional study.Place and Duration of Study: Department of Rheumatology, Liaquat National Hospital, Karachi, from Feb to May 2019. Methodology: All patients of age >18 years, of either gender, who presented with knee joint effusion were enrolled in the study. Synovial fluid aspiration for the analysis of lactate and lactate dehydrogenase (LDH) was done for all patients.Results: Seventy-seven patients were enrolled, of which 75 were included in the analysis. Two patients were excluded as one had lymphoma and the other had recent joint trauma. 31 (41.3 %) patients had non-inflammatory, or osteoarthritis, and 44 (58.7 %) had inflammatory arthritis. The mean value of synovial LDH in inflammatory and non-inflammatory arthritis was 737.38 ± 102.76 mmol/L and 265.5 ± 17.43 mmol/L, respectively, (p0.05).Conclusion: Synovial fluid lactic acid and synovial LDH can serve as rapid diagnostic and cost-effective tests to differentiate between non-inflammatory and inflammatory arthritis.